Spectrophotometric Determination of Copper(II) using 2,2[O-Tolidine-4,4-bis azo]bis[4,5-diphenyl imidazole](MBBAI) - ihsan Mahdi Shaheed (مجلة بغداد للعلوم, 2020)
Spectrophotometric method was developed for the determination of copper(II) ion. Synthesized (2,2[O-Tolidine-4,4-bis azo]bis[4,5-diphenyl imidazole]) (MBBAI) was used as chromogenic reagent at pH=5. Various factors affecting complex formation, such as, pH effect, reagent concentration, time effect and temperature effect, have been considered and studied. Under optimum conditions concentration ranged from (5.00-80.00) µg/mL of copper(II) obeyed Beer`s Low. Maximum absorption of the complex was 409nm with molar absorpitivity 0.127x104 L mol-1 cm-1. Limit of detection(LOD) and Limit of quantification were 1.924 and 6.42 μg/mL, respectively. The stoichiometric composition of the chelate is 1:2 (Cu:MBBAI). Experimental results for studying some selected ions as interference were reported. The developed method was successfully applied to determine copper (II) ion in dental filling.